2014
DOI: 10.1186/1752-1947-8-401
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthrosis causing altered mental status: a case report

Abstract: IntroductionCervical spondylosis as a cause of diaphragmatic weakness is an uncommon entity and has been reported primarily in the setting of cervical spinal cord compression. Cervical spondylosis most often causes respiratory failure from cervical myelopathy and damage to the ventral horn cells at spinal cord segments C3 to C5 from where the phrenic nerve arises. The manifestations are variable but there may be evidence of upper motor neuron signs and neurological deficits in the lower extremities along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Dyspnea is an extremely rare symptom in cervical spondylosis, making it difficult to diagnose alone. To our best knowledge, only 10 cases of phrenic nerve palsy associated with cervical spondylotic radiculopathy exist, including the present case [2][3][4][5][6][7][8][9][10] (Table 1), with nearly the same number of case reports associated with cervical myelopathy, [11][12][13][14][15][16][17][18][19] and some case series showed a declined respiratory function in cervical myelopathy. 20,21) Diagnosis of dyspnea associated with cervical spondylotic myelopathy is relatively straightforward because canal stenosis is easy to be recognized on radiological…”
Section: Discussionmentioning
confidence: 89%
“…Dyspnea is an extremely rare symptom in cervical spondylosis, making it difficult to diagnose alone. To our best knowledge, only 10 cases of phrenic nerve palsy associated with cervical spondylotic radiculopathy exist, including the present case [2][3][4][5][6][7][8][9][10] (Table 1), with nearly the same number of case reports associated with cervical myelopathy, [11][12][13][14][15][16][17][18][19] and some case series showed a declined respiratory function in cervical myelopathy. 20,21) Diagnosis of dyspnea associated with cervical spondylotic myelopathy is relatively straightforward because canal stenosis is easy to be recognized on radiological…”
Section: Discussionmentioning
confidence: 89%
“…[ 8 ] Moreover, EMG/NCS might provide evidence of degenerative neuromuscular diseases, such as amyotrophic lateral sclerosis or myopathy. [ 5 ] Unfortunately, neither EMG nor NCS were performed in our case.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies reported that electromyogram (EMG) and nerve conduction studies (NCS) might be helpful to diagnose hemidiaphragmatic paralysis. [ 5 , 8 ] Transcutaneous phrenic nerve stimulation in NCS shows a decrease in amplitude compared with the other side and EMG reveals radiculopathy, suggestive of nerve root compression. [ 8 ] Moreover, EMG/NCS might provide evidence of degenerative neuromuscular diseases, such as amyotrophic lateral sclerosis or myopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, there are only eight previously reported cases of phrenic nerve palsy secondary to cervical spondylosis, thus demonstrating the unusual nature of our case. [3][4][5] Seven cases report phrenic nerve palsy with myelopathy and one in the context of C5 radiculopathy. Our patient had no other discernible cause of diaphragmatic paralysis and the rationale for cervical spondylosis is compelling given the patient's cervical pathology at C3-C5, the origin of the phrenic nerve.…”
Section: Discussionmentioning
confidence: 99%